The Influence of the Central Asian Climate on the Strength Characteristics of Brick Masonry - Paizullaevna, Sanaeva Nargiza (Research Parks Publishing LLC, 2022)
The article presents the results of an experimental study of the influence of temperature and relative humidity of the environment and sunlight on the strength characteristics of brickwork. The strength of the masonry is greater the thicker the stone, as the resistance of the stone to bending and cutting increases. The more correct the shape of the stone, the greater the strength of the masonry, as there is a more uniform transfer of the load.